A Crisis‐Driven Migration? Aspirations and Experiences of the Post‐2008 South European Migrants in London. (30th April 2019) - Pratsinakis, Manolis; King, Russell; Himmelstine, Carmen Leon; Mazzilli, Caterina
Abstract: Since the 1990s young South Europeans have been attracted to London by the dynamic labour market and cultural radiance of the city, but also pushed by unfavourable conditions in the labour markets of their origin countries. Subsequently, the Eurozone crisis, austerity politics and their socio‐political consequences have markedly intensified migration rates. But did they also signify a rupture in terms of the motivations, experiences and aspirations of the migrants? Drawing on in‐depth interviews with Greek, Italian and Spanish migrants of different educational levels, we find that post‐materialist motivations and pro‐migration dispositions prevail among the "crisis‐migrants". Migration is seen and experienced as a step forward, rather than a disruptive force, signalling a positive message in defence of intra‐EU free mobility. Yet at times of neoliberal deregulation and economic and political uncertainty, aspirations for socio‐economic stability and settlement are also of growing importance, questioning mobility as the normative way of contemporary life.